Most important factors modelling health status of an individual and the population. Part 1 - Sobieszczańska, Anna; Sobieszczański, Jarosław; Piecewicz-Szczęsna, Halina; Słopiecka, Aleksandra; Zukow, Walery; Karwat, Irena Dorota (Journal of Education, Health and Sport, 2016)
Introduction Human state of health is determined by so many factors that despite numerous studies conducted in many countries worldwide it is not possible to define them unequivocally. Health and diseases are conditioned in various parts of the world in different ways, both of the total population and the individual. Undoubtedly, these are strong premises to continue studies in the direction of unification of the definitions of health, disease, and disability. In every country there is a different level of recognition of health problems of the population, their dimensions, causes and consequences, which should constitute knowledge to determine projects, strengthening and improvement of the quality of health care. Modern actions in the domain of health promotion, prophylaxis, as well as health education, are of primary importance in the modelling of the state of health. Objective The objective of the study was presentation of widely understood health and social factors, which may effectively influence the improvement of the state of health, both of an individual and the population, as evaluated in the sphere of health behaviours, availability and level of the health services offered, and the state of advancement of epidemiological knowledge while assessing positive and negative health measures. Description of the state of knowledge The data published in many scientific studies, mainly by the agendas of the World Health Organization, demonstrate that the factors shaping the level of human health include: incorrect life style, hazards within the physical environment, widely understood geographic factors (natural, climatic, which are specific in some latitudes), and the quality of care provided by health services. Many researchers have no doubt that from each of the large groups of factors it is possible to select smaller groups, the number and quality of which are characteristic or highly specific to various groups of people. Frequently, many factors shaping the level of health are underestimated, which exerts a negative effect on the quality improvement of widely understood health care over the individual and the population. Such factors include, among others, climatic processes, long-lasting body exposure to solar radiation, sunless weather, interpersonal communication, domains of human functioning especially threatened by long-term stress. Efforts oriented towards an improvement of the quality of health by individuals themselves will be insufficient without a systemic support provided for them through activities of health care teams functioning in the local environment. Good availability, not only of the actions classified into restorative medicine, but primarily preventive medicine, is a guarantee of the effective health promoting behaviours of large social groups. This is one of the factors which may determine a better state of health of the population within future years. Many epidemiological data and studies of the availability of health services indicate that the Polish system of health care requires profound reorganization. This is also confirmed by low positions in the ranking by the Euro Health Consumer Index, where in 2014, Polandoccupied the 31st position among the 37 investigated health care systems, while in 2015, it dropped to the 35th position. Summary Beneficial actions conducted towards modelling the state of health of an individual and the population may be obtained based on systematic achievements in clinical, epidemiological, environmental and sociological studies. They impose changes in defining public health, which, as a science, appropriates a growing number of new domains of knowledge and tasks supporting the improvement of many elements of life style. The character of health needs of an individual and the population changes, among others, as a result of progressing civilisation changes and unfavourable demographic or environmental changes. For years, inequalities in health have constituted a great problem in the improvement of the state of health. The main element in the struggle with this problem is the implementation of modern prevention programmes, which contribute to the reduction of morbidity and mortality due to many diseases, mainly of the cardiovascular system and cancer.